2011
DOI: 10.1186/1471-2458-11-s1-s7
|View full text |Cite
|
Sign up to set email alerts
|

A review of mathematical models of influenza A infections within a host or cell culture: lessons learned and challenges ahead

Abstract: Most mathematical models used to study the dynamics of influenza A have thus far focused on the between-host population level, with the aim to inform public health decisions regarding issues such as drug and social distancing intervention strategies, antiviral stockpiling or vaccine distribution. Here, we investigate mathematical modeling of influenza infection spread at a different scale; namely that occurring within an individual host or a cell culture. We review the models that have been developed in the la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
253
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(257 citation statements)
references
References 133 publications
(152 reference statements)
4
253
0
Order By: Relevance
“…This simple model and variants have been used in several recent analyses of influenza A virus within-host infection dynamics (e.g. [35,36] for reviews). The model tracks uninfected cells, U; infected cells, I; and free infectious virus, V. Cells become infected at rate k, infected cells produce virus at rate p and die at rate d. Free virus is cleared at rate d. The equations for uninfected cells, infected cells and free virus are given by dU/dt ¼ 2kUV, dI/dt ¼ 2kUV2dI and dV/dt ¼ pI2dV.…”
Section: Materials and Methods (A) Experimental Datamentioning
confidence: 99%
“…This simple model and variants have been used in several recent analyses of influenza A virus within-host infection dynamics (e.g. [35,36] for reviews). The model tracks uninfected cells, U; infected cells, I; and free infectious virus, V. Cells become infected at rate k, infected cells produce virus at rate p and die at rate d. Free virus is cleared at rate d. The equations for uninfected cells, infected cells and free virus are given by dU/dt ¼ 2kUV, dI/dt ¼ 2kUV2dI and dV/dt ¼ pI2dV.…”
Section: Materials and Methods (A) Experimental Datamentioning
confidence: 99%
“…The influenza model by Baccam et al (6) is the most parsimonious in vivo viral dynamics model reported and is based on the fundamental predator-prey concept: a pool of free virus infecting a susceptible pool of target respiratory epithelial cells. It is similar to the earlier models used to describe human immunodeficiency virus dynamics (7), but differs in that no turnover is assumed for the target cells because the duration of acute influenza virus infection (approximately 7 days) is much shorter than the life span of the target respiratory epithelial cells, an assumption which does not hold true for chronic infections such as AIDS or hepatitis C (7)(8)(9).…”
mentioning
confidence: 99%
“…Thus, mathematical modeling has been used to capture the dynamics of influenza virus infection and to understand the interaction of the virus with the immune system (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Much of the work has been focused on the basic relationship between the host and the virus (25,26,32,34,35), whereas other work has strived to quantify the interplay between viral replication and adaptive immunity (27)(28)(29)(30)36).…”
mentioning
confidence: 99%